Implementasi Kurikulum Merdeka Di SDN 25 Kota Ternate - Yetni Marlina (Peneliti.net, 2023)
The curriculum has an important role in the form of learning tools that contain planning of learning activities in the form of a process of acquiring knowledge and experience gained through a series of learning activities. This study aims to analyze the independent curriculum further by focusing on planning the implementation of the independent curriculum and learning planning on the independent curriculum at the elementary school level. This type of research is a qualitative research with a phenomenological approach. The qualitative design was implemented and carried out on school principals and grade 1 teachers and grade 4 teachers. Data collection techniques used interviews and document analysis. The data analysis technique used is the interactive model in which the elements include data reduction, data presentation, and data conclusion. The results of the study show that implementing the independent curriculum requires the readiness of school principals and teachers to learn new things. In the planning process, teachers still rely on teaching modules provided by the center. There are new things that must be considered in the independent curriculum with the project to strengthen the profile of Pancasila students. The implications of this research are that teachers are expected to be able to use the 21st century learning model in implementing the independent learning curriculum in schools.